The impact of co-fed plastic diet on Tenebrio molitor gut bacterial community structure - Larisa Ilijin; Dušanka Popović; Milica Živković; Dajana Todorović; Marija Mrdaković; Milena Vlahović; Vesna Perić-Mataruga (Scientific Reports)
Abstract This study aimed to analyze the long-term impact of co-fed plastic diet on the bacterial community of self-sustaining laboratory populations of T. molitor fed with wheat bran with added polystyrene (PS), and low density polyethylene (LDPE) over a three year period. The most abundant phyla for all three populations were Firmicutes, Bacteroidota and Proteobacteria. PS group microbiota is similar to C group, pointing to a common bacterial species capable for degrading lignocellulose and PS, while consumption of LDPE caused a significant decrease of Bacteroidota and Actinobacteriota compared to both C and PS group, and Campylobacterota compared to PS group. A predictive metabolomics analysis recognized dTDP-L-rhamnose biosynthesis I in PS group as one of five unique pathways, while other five distinctive pathways, like peptidoglycan maturation, were linked to LDPE group. Further studies are needed to determine the plastic degrading properties of the detected bacteria. The results highlight T. molitor’s versatility in biotechnological applications.